Respuesta :
3 consecutive even integers....x , x + 2, and x + 4
the first number equals the sum of the second and third....
x = (x + 2) + (x + 4)...combine like terms
x = 2x + 6 <===
the first number equals the sum of the second and third....
x = (x + 2) + (x + 4)...combine like terms
x = 2x + 6 <===
Answer:
The three numbers are -6,-4 and -2. The equation to solve the problem is x = 2x+6.
Step-by-step explanation:
If x is the smallest number, then the other two consecutive even numbers are x+2 and x+4. Now, as the first number is the sum of the second and the third we have that
x = x+2+x+4
x = 2x+6 (that is the equation that could be used to solve the problem)
x-2x = 6
-x = 6
x = -6.
Then, the three numbers are -6,-4 and -2.